(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of febrile neutropenia in children with leukemia admitted in the department of child health KTH Peshawar. Study Design: Descriptive / cross-sectional study. Place and Duration of Study: This study was conducted at the Department of pediatrics, Khyber teaching hospital, Peshawar from March 2016 to September 2017. Materials and Methods: 50 patients of acute leukemia (subtypes of ALL and AML) were selected through non randomized convenient sampling. Before enrolling the patient informed consent was taken from the attendant. Detailed history and examination was performed and full blood count was sent to Khyber Teaching Hospital laboratory. Common clinical features were noted along with hematological parameters. Standardized management protocols were applied to these patients. Results: Out of 50 patients 31 were male and 15 were female that presented with acute lymphoblastic leukaemia and 4 patients were of acute myeloid leukaemia with two patients male and 2 female. Out of 50 patients 17 cases presented with febrile neutropenia, out of these 12 patients were male and 5 patients were female. 16 patients with febrile neutropenia were Acute lymphoblastic leukemia while 1 patient had Acute myeloid leukemia. 9 patients were between age range of 1-5 years, 7 were between 5-10 years, 1 patient was over 10 years age and no patient less than 1 year presented with febrile neutropenia. Pallor and fever were the most common presenting complaints followed by organomegaly. Other clinical features which were present were lymphadenopathy bruises and patechia, bone pain and tenderness abdominal pain and vomiting. Conclusion: In our study out of 50 patients 31 were male and 15 were female that presented with acute lymphoblastic leukemia and 4 patients were of acute myeloid leukemia with two patients male and 2 female. 17 cases presented with febrile neutropenia, out of these 12 patients were male and 5 patients were female. 16 patients with febrile neutropenia were Acute lymphoblastic leukemia while 1 patient had Acute myeloid leukemia. 9 patients were between age range of 1-5 years, 7 were between 5-10 years, 1 patient was over 10 years age and no patient less than 1 year presented with febrile neutropenia. Fever was presenting complaint in all the patients comprising 100% patients, followed by pallor, hepatomegaly and splenomegaly